The role of digitalization in the internationalization process of a traditional SME - Soikkeli, Niina (My University, 2023)
The emergence of digital technologies and the on-going digital transformation accelerated by the Covid-19 pandemic has presented also traditional SMEs opportunities to exploit the advantages of digitalization in their internationalization process. Although, digitalization and its connection to entrepreneurship have been studied by various researchers, there are few studies examining the phenomenon from the perspective of an SME and even less focusing on the traditional SMEs. The objective of the study is thus, to fill the research gap and extend the research to examine the role of digitalization in the internationalization process of a traditional SME. The term traditional SME is used in this study to describe a small and medium -sized enterprise trading consumer goods and services that exist in the physical dimension. The research was conducted in a form of a qualitative case study consisting of three Finland-based companies. The study was further supported by a literature review focusing on theoretical research around digitalization, internationalization, and the relationship between those two topics. The study’s aim is to answer the research question “How can digitalization advance the internationalization process of a traditional SME?”. The study’s findings show that digitalization has an enabling role in the internationalization process of a traditional SME. According to the results, digitalization can advance the internationalization process in terms of decreased risks related to foreign market selection, increased reach of wide audiences in a cost-efficient manner, and possibilities to swiftly implement data-based marketing decisions to support revenue creation. Additionally, remote operations enabled by digitalization create new international business opportunities and allow traditional SMEs to generate direct international sales. Lastly, digitalization enables resource-efficient internal and external value creation. The findings further emphasize the significance of the companies’ entrepreneurial orientation towards digitalization, appropriate capabilities, and sufficient resources in order to benefit from the opportunities presented by digitalization.

Digitaalisten teknologioiden kehitys ja meneillään oleva Covid-19-pandemian kiihdyttämä digitaalinen transformaatio ovat luoneet mahdollisuuksia myös perinteisille pienille ja keskisuurille yrityksille (pk-yrityksille). Yksi näistä mahdollisuuksista on digitalisaation hyödyntäminen pk-yritysten kansainvälistymisessä. Digitalisaatiosta ja sen yhteydestä yrittäjyyteen on tehty lukuisia tutkimuksia, mutta ilmiötä ei ole juurikaan käsitelty pk-yrityksen saatikka perinteisen pk-yrityksen näkökulmasta. Tutkielman tarkoituksena on laajentaa aikaisempaa digitalisaation tutkimusta ja selvittää digitalisaation roolia perinteisten pk-yritysten kansainvälistymisprosessissa. Tässä tutkielmassa termillä “perinteinen pk-yritys” tarkoitetaan pieniä ja keskisuuria yrityksiä, jotka toimittavat fyysisessä muodossa olevia tuotteita ja palveluita. Tutkielma suoritettiin laadullisena tapaustutkimuksena, joka koostui kolmesta suomalaisesta yrityksestä. Tämän lisäksi tutkielma hyödyntää digitalisaatiota, kansainvälistymistä ja näiden kahden aiheen suhdetta käsittelevää teoreettista tutkimusaineistoa. Tutkielman tavoitteena on vastata kysymykseen “Miten digitalisaatio voi hyödyttää perinteisen pk-yrityksen kansainvälistymisprosessia?” Tutkimustulokset osoittavat, että digitalisaatiolla on avustava rooli tutkimuskohteiden kansainvälistymisessä. Tulosten mukaan digitalisaatio voi hyödyttää kansainvälistymisprosessia usealla tavalla: vähentäen ulkomaan markkinavalintaan liittyviä riskejä, kasvattamalla kustannustehokkaasti suurten yleisöjen saavutettavuutta, ja mahdollistamalla nopeiden dataan perustuvien markkinointipäätösten implementoinnin tuloksen kasvattamiseksi. Lisäksi digitalisaation mahdollistamat etätoiminnot luovat uusia kansainvälisen liiketoiminnan tilaisuuksia sekä antavat perinteisille pk-yrityksille kyvykkyyden kansainvälisten suorien tulovirtojen muodostamiseen. Kaiken tämän lisäksi digitalisaatio toimii alustana resurssitehokkaalle sisäiselle ja ulkoiselle arvon luomiselle. Tulokset korostavat lisäksi organisaatioiden digitalisaatioon suuntautuvan yrittäjämäisyyden, soveltuvien kyvykkyyksien ja riittävien resurssien merkitystä digitalisaation tuomien mahdollisuuksien hyödyntämisessä.
Keywords: pienet ja keskisuuret yritykset; kansainvälistyminen; digitalisaatio; small and medium-sized enterprises; digitalisation; internationalisation; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business